Grassroots practices of citizenship and politicization in the urban: the case of right to the city initiatives in Barcelona. Issue 5 (4th July 2018) - Islar, Mine; Irgil, Ezgi
ABSTRACT: This article aims to produce an analysis of the politicization of the citizens after Spain's Indignados movement from a citizenship framework. The article suggests that claiming the right to the city involves more than issues of access to urban amenities: it is also about claiming the right to participate in the formation and transformation of the city and the right to appropriate the city center. This positions these rights within the larger issue of citizenship by defining it as a collective practice rather than a state-sanctioned status. Our analysis is based on the empirical evidence derived from the semi-structured interviews, politicians' speeches, information based on media resources and official websites, and participant observation during three months of fieldwork in Barcelona in 2016.